LEAF RUST RESISTANCE IN COMMON WHEAT VARIETIES AND LINES FROM THE COLLECTION OF THE VAVILOV PLANT INDUSTRY INSTITUTE CARRYING ALIEN GENETIC MATERIAL - A. S. Sadovaya; E. I. Gultyaeva; O. P. Mitrofanova; E. L. Shaidayuk; A. G. Hakimova; E. V. Zuev (Вавиловский журнал генетики и селекции)
Leaf rust resistance was estimated in 83 common wheat accessions from the collection of the Vavilov Institute carrying alien genetic material. Eight accessions with seedling resistance and 27 accessions with adult plant resistance were found. Analysis with molecular markers revealed genes highly and moderately efficient in Russia – Lr24, Lr39, Lr21, and Lr37 – and a rye translocation 1AL.1RS. The samples accessions effective Lr genes are promising donors in Russian breeding programs. Lines raised with the use of T. timopheevii were heterogeneous for resistance. No molecular markers of the Lr50 gene known for this species were detected there. These lines demand further examination and selection.